Investigating the impact of onion-like carbons on the supercapacitance of Ti2CTx MXene - Habib, Irfan (My University, 2019)
Increasing energy demands in contemporary society have driven research in energy storage to create devices which emphasize both energy density and power density. The supercapacitor is a key example of such a device. It is a broad category of devices that occupies the middle ground between batteries and capacitors. The purpose of this work is to present a detailed understanding of supercapacitors via an investigation into a new class of 2D materials called MXenes as an active electrode material for supercapacitor applications. More speci cally, the titanium carbide MXene, Ti2C, was investigated as a supercapacitor active material, as well as the in uence of another nanomaterial, carbon onions or onion-like carbons (OLCs), as a dopant. The materials were characterised by a number of physical techniques; including X-ray Di raction (XRD), Raman Spectroscopy, Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), X-ray Photoelectron Spectroscopy (XPS), and Brunauer{Emmett{Teller surface area analysis (BET). The materials were also characterised using electrochemical techniques such as Cyclic Voltammetry, Constant Current Charge/Discharge, and Electrochemical Impedance Spectroscopy. It was found that the introduction of OLCs into the layered MXene structure increases the long term cycling stability of the material from 80% to > 95% when used in 5% and 10% weight percentages. It was also found to increase the supercapacitance of the MXene in the 5% quantity from 104 F/g to 148 F/g, but decreased the supercapacitance in the 10% quantity from 104 F/g to 92 F/g. This power and energy density also improved in the 5% OLC doped sample compared to the pristine sample for current densities between 0.5 A/g and 5 A/g. Overall, this study showcased the ability of OLCs to improve electrochemical performance of a Ti2C based supercapacitor